Biochemical parameters (lactate dehydrogenase, serum albumin) as early predictor of severe dengue - Shankar, Poornima; B., Prarthana (International Journal of Contemporary Pediatrics, 2017)
Background: Dengue fever (DF) is the arboviral infection with the largest incidence worldwide. Clinical expression of dengue virus infection varies from no symptoms to severe dengue with shock. It is the most rapidly spreading vector borne disease in the world. Nearly 100 million cases of Dengue fever and between 250,000 and 500,000 cases of severe dengue are annually reported to the WHO. The objective of this study was to study aims at determining the LDH and serum albumin levels as early parameter to predict the severity of Dengue illness. Methods: A observational clinical study conducted at K.I.M.S hospital, Bangalore, Karnataka, a tertiary care hospital. Children admitted in KIMS Hospital, Bangalore, Karnataka, a tertiary care hospital, Serum LDH and serum albumin levels are measured using the blood sample taken on the 3rd day of fever after confirmation of dengue fever (NS1 Ag- positive). Results: Study enrolled 150 patients with confirmed infection of Dengue virus who were admitted to paediatric unit between July 2014 and December 2016. Serum samples taken 72-96 hours within onset of fever were used for biochemical tests. Of 150 patients, 40 developed Severe Dengue (SD). Cases of SD had higher levels of lactate dehydrogenase (LDH) and low levels of serum albumin. Multivariate analysis showed that early alterations of LDH levels i.e. Out of 40 patients who developed severe dengue, 37 patients i.e. 92.7% had raised levels of LDH with levels more than >600 IU and<3 levels of serum albumin 13 patients i.e 32.5% of severe dengue cases with P value of < 0.001, which showed significant association. Conclusions: Early alterations of biochemical parameter like LDH and serum albumin can predict Severe Dengue in patients with acute dengue illness.